2018
DOI: 10.1055/a-0647-2021
|View full text |Cite
|
Sign up to set email alerts
|

4D-Flow MRI: Technique and Applications

Abstract: ABSTR AC TBackground Blood flow through the cavities of the heart and great vessels is pulsatile and is subject to time and multidirectional variations. To date, the recording of blood flow in multiple directions and phases has been limited. 4D-flow MRI offers advantages for the recording, visualization and analysis of blood flow.Method The status quo of the method was summarized through analysis with the PubMed database using the keywords "4D-flow MRI, phase-contrast magnetic resonance imaging, MR flow imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
0
31
0
1
Order By: Relevance
“…[33][34][35][36] In summary, 4D flow MRI can be a useful tool as an add-on to standard MRI sequences for investigating the relationship between carotid stenosis and cerebral hemodynamics and optimize patient selection and reduce the need for other testing. [37] The distribution of cerebral blood flow after CEA Changes in cerebral hemodynamics after CEA or carotid artery stenting (CAS) are dependent on the timing of the blood flow measurement. Previous studies have found postoperative increases in CBF, blood flow velocity and BFR hours to days after CEA or CAS.…”
Section: Possible Clinical Applications For Flow Mrimentioning
confidence: 99%
“…[33][34][35][36] In summary, 4D flow MRI can be a useful tool as an add-on to standard MRI sequences for investigating the relationship between carotid stenosis and cerebral hemodynamics and optimize patient selection and reduce the need for other testing. [37] The distribution of cerebral blood flow after CEA Changes in cerebral hemodynamics after CEA or carotid artery stenting (CAS) are dependent on the timing of the blood flow measurement. Previous studies have found postoperative increases in CBF, blood flow velocity and BFR hours to days after CEA or CAS.…”
Section: Possible Clinical Applications For Flow Mrimentioning
confidence: 99%
“…Thanks to development of new and high resolution imaging techniques like time-resolved three-dimensional phase contrast MRI (Kozerke et al, 2001;Frydrychowicz et al, 2007) also known as 4D flow MRI, hemodynamics have gained attention in the BAV field. This technique allows quality and quantitative flow measurement, like flow velocity, flow direction, wall shear stress, complex flow patterns, etc (Sträter et al, 2018). The progress of development of new imaging techniques in the cardiovascular field has also helped acquire more fast and accurate data in order to obtain prognosis or diagnosis of several diseases.…”
Section: Hemodynamics Alterations In Bav Diseasementioning
confidence: 99%
“…Quantitative flow analyses are obtained by placing arbitrary analysis planes using the 4D flow MRI-derived angiograms for correct orientation. 4D flow MRI-derived analyses of time-resolved flow velocities and flow rates are made equivalent to 2D phase contrast flow measurements: a local acceleration of flow velocity indicates a stenosis and a reduced flow rate indicates a reduced blood supply of the downstream organ [1]. If spatial resolution suffices to visualize a reliable flow profile within the vessel lumen, helical and vortical flows, flow eccentricity, and wall shear stress (WSS) can be evaluated [13].…”
Section: D Flow Mri Data Analysismentioning
confidence: 99%
“…1A, ▶ Video 1A). Velocity-coded angiograms can be obtained for each timeframe and are visualized as pathlines or streamlines within the vessel lumen [1] (▶ Fig. 1B, ▶ Video 1B).…”
Section: D Flow Mri Data Analysismentioning
confidence: 99%
See 1 more Smart Citation